{The Use of Norethisterone for the Treatment of Severe Uterine Bleeding in Adolescents: An Audit of Our Experience} - Papapanagiotou, I.K.; Charamanta, M.; Roidi, S.; Al-Achmar, N.S.; Soldatou, A.; Michala, L. (Journal of Pediatric and Adolescent Gynecology, 2019)
© 2019 North American Society for Pediatric and Adolescent Gynecology Study Objective: The purpose of this prospective study was to assess the effectiveness of norethisterone (NET) in the management of abnormal uterine bleeding (AUB) in adolescents in a tertiary care center. Design: This was a prospective audit focused on administering high doses of NET in female adolescents with complaints of AUB. Setting: We included female adolescents who presented to our Emergency Gynecological Department or Adolescent Gynecological Outpatient Department from October 2016 to January 2019. Participants: The study included 29 female adolescents aged 11-17 (mean, 13.14) years. Interventions: Patients were administered a daily dose of 10-30 mg, depending on the severity of the condition, bleeding duration, and patient weight. Main Outcome Measures: Cessation of vaginal bleeding. Results: Mean age at menarche of our patient sample was 11.4 years (range, 10.7-14 years). AUB presented at a mean time of 24.6 months after menarche (range, 0-79 months). Blood transfusion was deemed necessary in 9 patients. Bleeding stopped at a mean of 46.1 (range, 8-120) hours after onset of treatment with NET. No serious adverse events were reported with NET administration, with only 3 cases of minor side effects. Conclusion: The use of NET is an effective and reliable treatment option among adolescents for whom control of AUB is desired in the acute setting.
Keywords: Abnormal uterine bleeding; Adolescents; AUB; Heavy menstrual bleeding; norethisterone